Secure Data Validation and Transmission in Cloud and IoT Through Ban Logic and KP-ABE - Kumar, Narander; Samriya, Jitendra K. (International Journal of Sensors Wireless Communications and Control, 2022)
Background: Cloud computing is a service that has undergone accelerated growth in the field of information technology in recent years. Privacy and security are challenging issues for cloud users and providers. Objective: This work aims at ensuring secured validation of user and protecting data during transmission for users in a public IoT-cloud environment. Existing security measures have failed by their single level of security, adaptability for a large amount of data and reliability, to overcome these issues and to achieve a better solution for vulnerable data. Methods: The suggested method utilizes secure transmission in the cloud using key policy attributebased encryption (KP-ABE). Initially, user authentication is verified. Then the user data is encrypted with the help of KP-ABE algorithm. Finally, data validation and privacy preservation are done by Burrows-Abadi-Needham (BAN) logic. This verified, shows that the proposed encryption is correct, secure and efficient to prevent unauthorized access and prevents data leakage with fewer chances of data/identity theft of a user as this analysis performed by KP-ABE is based on access control approach. Results: Here, the method attains a maximum of 88.35% of validation accuracy with a minimum 8.78ms encryption time, which is better when compared to the existing methods. The proposed mechanism is done by MATLAB. The performance of the implemented method is calculated based on the time of encryption and decryption, execution time and validation accuracy. Conclusion: Thus, the proposed approach attains high IoT-cloud data security and increases the speed for validation and transmission with high accuracy and is used for cyber data science processing.
Keywords: IoT